Literature Review: Bahan Lokal Indonesia sebagai Bahan Baku untuk Optimasi Kandungan Beras Analog Pengganti Beras Padi - Desy Sonya Putri; Heny Kusumayanti (Universitas Airlangga, 2023)
Background: The majority of people in Indonesia make rice as a staple food. From the large consumption of paddy rice, there is an alternative to overcome dependence on rice by developing analog rice. Analog rice is artificial rice with raw materials that contain high carbohydrates. Raw materials for making analog rice must contain structural forming materials such as dispersed phases, thickeners, flavor enhancers, and leavening agents. Some of the main ingredients of analog rice include cassava, gembili, and sweet potatoes. Objective: The purpose of this study was to determine the content and types of local ingredients that can be used to make analog rice as a substitute food for paddy rice Method: This research uses Systematic Literature Review from national and international journals Results: There are various materials with perfect nutritional content that must be contained in analog rice. Conclusion: Analog rice is an alternative solution to the problem of the Indonesian people's dependence on rice. Analog rice must be considered a constituent material to have a perfect nutritional content. Indonesian local ingredients such as cassava, gembili tubers, and sweet potatoes can be used as analog rice staples